A New One-Pot Synthesis of 3,6-Disubstituted Pyridazines Starting from β-Nitro-β,γ-Unsaturated Ketones - Khan, Muhammad E. I.; Yuan, Lixia; Petrini, Marino; Palmieri, Alessandro (Synthesis, 2023)
A new one-pot preparation of 3,6-disubstituted pyridazines starting from β-nitro-β,γ-unsaturated ketones and hydrazine monohydrate is presented. The protocol entails two sequential steps, leading to the isolation of the title targets in satisfactory overall yields tolerating a good variety of additional functionalities.
Keywords: pyridazines; heterocycles; cyclization; nitroolefins; one-pot